Adverse reactions from prolonged use of oral contraceptives (Research, Society and Development, 2022)
The use of contraceptives is a practice for which there is a large adherence, however, such procedure can bring risk when the chronic use and not prescribed by a medical professional, and, even with the appropriate prescription, the lack of monitoring of the use can increase the risks of occurrence of adverse reactions. The present study is an exploratory, analytical research, which aimed to evaluate the pattern of use of oral contraceptive medications (OC) by women and specifically the occurrence of adverse reactions arising from the use of these medications, by sharing a questionnaire in social media, with questions about adherence to contraceptive therapy and how the use of such medications by women who agreed to participate in the research. It was observed that, of a total of 233 women who agreed to participate in the research, 65.4% had been using contraceptives for a period between 5 and 10 years. It was also possible to observe that 63.2% of them had headache as the predominant adverse reaction (P